Nano-sized carriers in gene therapy for peritoneal fibrosis in vivo. (1st January 2017) - Igarashi, Yusuke; Hoshino, Taro; Ookawara, Susumu; Ishibashi, Kenichi; Morishita, Yoshiyuki
ABSTRACT: Peritoneal fibrosis is a crucial complication in patients receiving peritoneal dialysis. It is a major pathological feature of peritoneal membrane failure, which leads to withdrawal of peritoneal dialysis. No specific therapy has yet been established for the treatment of peritoneal fibrosis. However, gene therapy may be a viable option, and various nano-sized carriers, including viral and non-viral vectors, have been shown to enhance the delivery and efficacy of gene therapy for peritoneal fibrosis in vivo . This review focuses on the use of nano-sized carriers in gene therapy of peritoneal fibrosis in vivo .